Caracterización clínica y epidemiológica del Síndrome de Sjögren. - Ambuludi Medina, Tania Maritza (2024)
Sjögren's syndrome (SS) represents an intriguing medical challenge, being a multisystem autoimmune condition, the medical relevance of this disease lies in its ability to generate symptoms that go beyond glandular manifestations, affecting multiple organ systems, becoming a diagnostic challenge. The objective of the study was to determine the epidemiological and clinical characterization of patients suffering from Sjögren's Syndrome to provide adequate management, through a literature review. A systematic bibliographic review of scientific articles that involved SS as the main topic was carried out. After applying inclusion and exclusion criteria, the sample consisted of 41 articles that met the required scientific quality standards. The results obtained allowed us to determine that Sjögren's syndrome is a multisystem disorder, which presents as risk factors patients with viral infections and a family history of autoimmune diseases. All articles agree on the female sex as a predisposing risk factor above the male sex. and those articles that identify SS in children associate it with a family history risk factor; The most frequent clinical manifestations are xerophthalmia, xerostomia, cutaneous manifestations and musculoskeletal pain in 92.7%, the population that receives initial treatment with glucocorticoids is 80.5% and 19.5% see their quality of life affected by fatigue, anxiety and depression. Conclusion: SS has as a risk factor the female sex and patients exposed to viral infectious diseases, it is rarely identified in children; It manifests mainly with xerophthalmia and xerostomia, however, there may be various systemic alterations. In most cases, the initial treatment is symptomatic and antiinflammatory; This syndrome can affect the quality of life of patients, even causing disability.